Prophet Muhammad and His Western Critics: By 'Zafar Ali Qureshi. Mansoorah, Pakisan: ldara Ma'arif lslami, 1992, 2 vols. (American Journal of Islam and Society, 1997)
Modem Orientalists generally boast of their objective analysis and impartialapproach to problems, but facts believe their loud claims when their researchcomes down to the study of the Prophet. In this case, deep prejudices are reflectedin their writings. Sometimes they indulge in frontal attacks on him, whileat other times they hit him below the belt. They try to give an impression thatthe time in which the message of Islam was spread was ripe for revolution, independentof the Prophet. So to them, the Prophet's contribution was to make a correct assessment of the prevailing situation and then make use of the opportunityprovided to project his viewpoint. The ultimate aim of such endeavors onthe part of Orientalists is to belittle the historic role of the Prophet and to unsettlethe Muslim consciousness of its cognitive certainty of the divine revelationto the Prophet.The author asserts that the Prophet brought about a complete revolution inthe lives of his early followers. After embracing Islam, they no longer remainedthe old Arabs they became God-fearing and pious folk who were very concernedwith the life hereafter rather than riveting their attention on material considerations.In view of these realities, it is highly callous on the part of ReverendWatt to denigrate Muslims for what they sought to accomplish. No fair-mindedhistorian would point out any character failing in these noble men. Also, theycould not simply think of invading neighboring lands, as Watt would have usbelieve. Likewise, Watt’s whole chain of hypotheses about the economic andpolitical reasons for the emigration to Abyssinia is without foundation ...